New records of leafhoppers and planthoppers of Slovenia (Hemiptera: Auchenorrhyncha) - Schürrer, Brigit (Acta entomologica slovenica (Ljubljana), 2003)
As a result of several sampling excursions in the year 2001, 40 species of 3 families are added to the list of the Auchenorrhyncha species of Slovenia. This increases the number of species recorded from Slovenia to 418.
Keywords: entomologija; Slovenia; Slovenija; škržatki